FENOMENA PELAKSANAAN IBADAH PUASA RAMADAN DI KALANGAN MASYARAKAT - Nasron HK; Oci Anggraini; Neli Julita; Vania Salsabila Faraghita; Imelda Herdianti; Ersa Enzelita; Karini Pebrianti; Riani Kusuma Fitri; Narzihatman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the phenomenon of Ramadan fasting among the public and the factors influencing it. Ramadan fasting is obligatory for every Muslim who is physically and religiously able. However, in practice, some people still do not fully observe the fast. This study used a qualitative method with a descriptive approach through interviews with several informants from diverse social backgrounds, such as daily laborers, farmers, the elderly, and adolescents. The results show that fasting is influenced by various factors, including economic conditions, the type of heavy work, health, social environment, and level of religious understanding. Some people do not fast due to the demands of their jobs, limited knowledge of religious concepts such as sahur (pre-dawn meal), qadha (qada), and fidyah (fasting), and health conditions such as chronic illness and advanced age. On the other hand, some informants still strive to observe the fast according to their abilities. This study also found that an educational and empathetic approach to providing religious understanding can increase public awareness of fasting. Thus, the phenomenon of some people not fasting is not solely due to weak faith, but rather a result of complex social and economic conditions. Therefore, contextual and humanistic da'wah strategies are needed to improve people's understanding and practice of religion.